Do legal and institutional environments matter for banking system performance?. Issue 1 (1st January 2020) - Arias, José; Maquieira, Carlos; Jara, Mauricio
Abstract: Using data on 52 countries' banking systems from 2005 to 2014, we explore how the legal and institutional environment influences banking system performance. Using panel data and controlling for financial and economic development indicators, we find evidence of several relationships related to banking system performance. First, a higher degree of legal protection for both lenders and borrowers positively affects banking system performance. Second, there is a positive relationship between the degree of law enforcement and banking system performance. Third, better regulatory quality positively affects banking system performance. Fourth, neither the degree of information sharing nor the control of corruption has a significant effect on banking sector performance. Finally, we find no significant differences in banking sector performance by type of economy.